POTENSI DAUN KATUK SEBAGAI PENURUN KADAR LEMAK PADA PRODUK UNGGAS MELALUI SKRINING FITOKIMIA - Novia Rahayu; Firgian Ardigurnita (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2021)
Katuk leaves are known as vegetables that are rich in nutrients in several regions in Indonesia. In addition, it has the potential as an herbal medicine that needs to be developed based on its chemical compound content. The groups of chemical compounds contained in plants can be analyzed using a phytochemical screening test. Phytochemical screening was carried out on katuk leaf extract samples obtained through the maceration method using methanol solvent which was then concentrated using a rotary evaporator. Phytochemical screening test consisted of phenolic, tannin, flavonoid, saponin, triterpenoid, steroid, and alkaloid screening. Furthermore, the test results will be used as a basis for researchers in developing the potential of katuk leaves as herbs to reduce fat content in poultry product. The class of compounds, especially flavonoids, saponins, and tannins has a role in reducing fat accumulation. The test results showed that the positive katuk leaf extract contained moderate amounts of phenolic compounds, tannin, flavonoids, saponins, triterpenoids, and alkaloids. That is, katuk leaves have the potential as an herb that can reduce fat levels in poultry products.